Study of the origin and correction of compass measurement errors in Doppler current meters - Le Menn, Marc; Lefevre, Dominique; Schroeder, Katrin; Borghini, Mireno (Frontiers in Marine Science, 2023)
Surface and subsurface currents are two of the Essential Climate Variables (ECVs) defined by the Global Climate Observing System (GCOS). In situ current measurements can be made by Eulerian methods with instruments on moorings fixed in space. These methods require the determination of two metrological quantities: the speed and the direction of the motion. Their measurement and calibration require the determination of reference velocities and the measure of the angular movement of seawater in relation to the measuring device, as well as of the measuring device in relation to a reference direction given by the magnetic North. This reference direction is determined by electronic compasses integrated into current meters and current profilers. Compasses are sensitive to their magnetic environment, and, therefore, to the objects and instruments that surround them. This publication describes experiments conducted with current meters and current profilers to measure the influence of different devices on the accuracy of their compass measurements. It gives some explanations about the origin of measurement errors and proposes solutions to correct or attenuate the defaults in direction measurements and the measured deviations. Correction formulas are given that can be applied to measured data. They allow the reduction of errors of several tens of degrees for data to be within the instrument’s specifications.